2013
DOI: 10.3896/ibra.1.52.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Standard use of Geographic Information System (GIS) techniques in honey bee research

Abstract: SummaryGeographic Information Systems (GIS) have been used in various fields and disciplines to summarize and analyse spatial patterns and distributions, for the purpose of understanding how geographic and non-geographic entities interact with each other over space and time.Although honey bees are directly related to and influenced by their local environment, few studies have incorporated honey bee data into GIS for the purposes of gauging these spatial relationships. This paper will briefly discuss some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The newly projected layer will then be automatically loaded to the project. See Rogers and Staub (2013) for a more extensive review of the basic tasks in QGIS.…”
Section: Main Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly projected layer will then be automatically loaded to the project. See Rogers and Staub (2013) for a more extensive review of the basic tasks in QGIS.…”
Section: Main Datasetmentioning
confidence: 99%
“…Another review by provided guidelines for GIS use in livestock genetics and enumerate the advantages of integrating data in a GIS environment. More recently, Rogers and Staub (2013) outlined spatial analyses and GIS methods in honey bees research. Their review is not specific to bees but instead aim to intensify the exploration of the spatial component of studies in ecology and related disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Due to predominance of mustard flora in Rajasthan, it was observed that mustard honey had lower amount of sucrose compare to other floral honeys. After comparing three states, it was observed that sucrose percentage varied between 0.45% to 2% with small number of samples falls between 2% to 3% of sucrose in all three states [42]. The lower percentage of sucrose was in Rajasthan followed by Punjab.…”
Section: Sucrose In Different Honey Samplesmentioning
confidence: 99%
“…The risks these declines pose to agriculture requires a strong focus on improving management of the industry. Due to the close relationship between honey bees and their surroundings there is scope to exploit the value of geospatial information through the use of geographic information systems (Rogers and Staub, 2013).…”
Section: Introductionmentioning
confidence: 99%